Combustibility studies of unsaturated polyester resins modified by nanoparticles - Zatorski, W.; Sałasińska, K. (Polimery, 2021)
Unsaturated polyester resin (UP) – based polymer composites with selected nanoparticles, including carbon nanotubes, aluminosilicates, polyhedral oligomeric silsesquioxane, and titanium dioxide, were synthesized. The flammability and smoke emission of the resulting products were characterized using cone calorimetry. The reduction in flammability of the nanocomposites was observed when compared to the non-filled resin. Depending on the nanoparticle type, different effectiveness in reducing emission of fumes from the burning nanocomposites has been achieved. The most promising fire-retarding effect was observed in case of the UP modified by nanometric titanium dioxide.